Factors Influencing Non-Performing Loans in State-Owned Banks’ Consumer Loans in Indonesia - Mulyono, Ellen; Pimada, Laila Masruro (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2026)
This research aims to examine the factors that influence Non-Performing Loan (NPL) consumer credit at state-owned banks in Indonesia. In this study, consumer credit refers to loans granted by banks to consumers, while Non-Performing Loan consumer credit refers to consumer credit that experiences repayment problems. Consumer credit base interest rate, the amount of consumer credit distribution, the consumer price index, the residential property price index, and the debt service ratio act as independent variables, and the Non-Performing Loan consumer credit variable stands as the dependent variable. The data used are annual panel data from the period of 2011–2023, and the analysis uses the panel-data regression method of the common effect model. The results of the study indicate that the consumer credit base interest rate, the consumer price index, the residential property price index, and the debt service ratio do not have a significant effect, while the amount of consumer credit distribution and the residential property price index have a significant effect on Non-Performing Loan consumer credit. This study provides the importance of state-owned banks to maintain the quality of consumer credit portfolios.